Evaluating seabed habitat representativeness across a diverse marine protected area network on the Mid-Atlantic ridge - Figueras, David Milla (2020)
Marine ecosystem-based management requires good spatial information on the distribution of marine species and habitats. Because such information is often limited to a few sampled locations, modelling techniques can be applied to produce predictive distribution maps. Harmonized broad-scale seabed habitat map was recently produced for Europe under the EMODnet Seabed Habitats programme. This new information was used to produce an extentbased evaluation of the representativeness and level of protection conferred by the current MPA network in the Azores (mid-north Atlantic ridge) to the variety of benthic marine habitats found in this region. A more objective assessment of the protection provided to these habitats was obtained by applying a scoring system to the MPAs based on the number of allowed extractive and non-extractive human activities, and on their potential impact on marine biodiversity and habitats. Results show that habitats protected by the network are nearly entirely classified as highly protected. In total, 26 habitats (including seven endangered and two rare) meet the Aichi Biodiversity Target 11 of 10% of coastal and marine areas protected by 2020. However, another 29 habitats fail to meet even the lowest target (four on-shelf habitats and 25 deep-sea habitats). These results highlight the need to extend effective protection levels to bathyal and abyssal habitats and to apply adequate ecological coherence criteria in the region. This approach sets a standard than can be used wherever similar information is available, be it in other European regions or beyond.